Digital innovation in SMEs : A Systematic Review, Synthesis and Research Agenda - Ramdani, Boumediene; Raja, Siddhartha; Kayumova, Marina (Taylor and Francis, 2022)
This paper presents a systematic literature review on digital innovation in Small and Medium-sized Enterprises (SMEs). It aims to synthesize previous research and identify knowledge gaps and future research opportunities. A systematic review of the literature was carried out by analyzing 382 articles published between 1979 and 2019. From synthesizing the extant literature, we developed a theoretical framework advocating that digital innovation in SMEs is driven by a configuration of antecedents, goes through different stages of innovation process, and leads to organizational and business process performance outcomes. Using an in-depth content analysis, we discuss the examined digital technologies, theories underpinning digital innovation in SMEs research, contextual orientations, and the content of research in this field. This review identifies significant knowledge gaps in relation to theory, context, method and content.